Encyclopedia of information communication technology - Cartelli, Antonio 1954-; Palma, Marco (Gale virtual reference library, 2009)
Describes the influence of information communication technology in scientific knowledge construction, with emphasis on the roles of product technologies, process technologies, and context technologies.